Analyses of working postures among malaysia pineapple plantation workers using ovako working posture analysis system - Nur Fazrina, Mohamad Salleh; Ezrin Hani, Sukadarin (Universiti Malaysia Pahang, 2018)
Ovako Working Posture Analysis System (OWAS) is a method which was extensively used in studying work postures. In this study, OWAS method was utilized to evaluate working postures of pineapple plantation workers on full job cycles in plantation and to determine if there was significant association with the prevalence of musculoskeletal symptoms among them. There were 103 pineapple plantation workers, with an average working experience of one to three years, participated in this study. Four major job activities of pineapple plantation were videotaped at the plantation and the process of analyzed was conducted afterward. OWAS identified for an overall distribution that planting, manual weed and harvesting were tasks which fell into category Action Category (AC) 3 which indicated distinctly harmful and AC4 which indicated extremely harmful. This study also identified there was a significant relationship between OWAS postural category and the prevalence of musculoskeletal symptoms of lower back and waist. To sum up, working in a pineapple plantation was a physical demanded job which involved poor prolonged postures. Consequently, some preventive actions must be applied to reduce the exposure.